EVALUASI PENERTIBAN PENAMBANGAN EMAS TANPA IZIN (PETI) DI SUNGAI KUANTAN KABUPATEN KUANTAN SINGINGI (STUDI KASUS PADA KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI) - Teti Febriza; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
PETI (Unlicensed Gold Mining) PETI is a mining business undertaken by an individual, a group of persons or companies whose operations are not licensed by a government agency. The problem of illegal mining is in Kuantan Mudik Subdistrict, where there are still many people doing mining activities and increasingly difficult to overcome. As for the parties - the authorities in handling this issue is the Integrated Control Team based on the Decree of the Regent of Kuantan Singingi Number 13 of 2013. There are several obstacles in the implementation of the control carried out by the Integrated Team in controlling the gold mining conducted by this community, among others, communication, funds and facilities, irresponsible persons, and the community. The concept of theory used by researchers is Evaluation. This research uses qualitative research methods, with descriptive data assessment. In collecting data, the researcher uses interview technique, observation, literature study and documentation, using key informant and informant afterwards as information source. The results of this study indicate that the ineffective implementation of PETI Control by Integrated Team of Penertiban is evident from the existence of people who conduct gold mining activities in the Kuantan Mudik Subdistrict of Kuantan Singingi Regency. Can be seen from the Evaluator indicator of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy.Keywords: Evaluation, Control, Gold Mining